2017
DOI: 10.17140/antpoj-2-111
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic and Demographic Correlates of Overweight and Obesity: A Study on the Karbi Women of Assam, Northeast India

Abstract: CitationMondal N, Timungpi R, Sen J, Bose K. Socio-economic and demographic correlates of overweight and obesity: A study on the Research ABSTRACTBackground: Excess adiposity is a chronic condition that contributes to non-communicable disease (NCD) related morbidities, mortalities and causes public health problems. Objectives: The objectives of the present community based cross-sectional study were to assess the prevalence of overweight and obesity and its socio-economic and demographic concomitants among a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Recent nutritional trend has shown that individuals/ populations belonging to the developing countries were observed to be particularly vulnerable to obesity-related diseases in addition to comorbidities. 13,21,59,60,61 In India, there is an increasing trend of dual burden of malnutrition (both undernutrition and over-nutrition) which needs proper management to control the epidemic within populations. It also requires assessments and establishment of the socio-economic, educational, environmental and cultural factors involved in determining overweight or obesity within populations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent nutritional trend has shown that individuals/ populations belonging to the developing countries were observed to be particularly vulnerable to obesity-related diseases in addition to comorbidities. 13,21,59,60,61 In India, there is an increasing trend of dual burden of malnutrition (both undernutrition and over-nutrition) which needs proper management to control the epidemic within populations. It also requires assessments and establishment of the socio-economic, educational, environmental and cultural factors involved in determining overweight or obesity within populations.…”
Section: Discussionmentioning
confidence: 99%
“…It also requires assessments and establishment of the socio-economic, educational, environmental and cultural factors involved in determining overweight or obesity within populations. 5,13,21,62,63,64 Majority of the Indian states have shown the prevalence of undernutrition among adults to varying between 20% and 29%. 65 Several studies have also reported high undernourishment among various Indian populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations